Comparing employment interviews in Latin America with other countries - Posthuma, Richard A.; Levashina, Julia; Lievens, Filip; Schollaert, Eveline; Tsai, Wei-Chi; Wagstaff, Maria Fernanda; Campion, Michael A. (Journal of business research, 2014)
This study compares job interviews (n=11,667) in Mexico with those in the following countries: Belgium, Russia, Taiwan, and the U.S. The findings support our hypotheses, which are based on a meta-cultural framework. The results reveal that in Mexico and Taiwan women are less likely to conduct interviews. In addition, interviewers asked different questions. Outside the U.S., interviewers asked applicants about their family, marital status, and children. In Russia and Taiwan, they asked about applicants' reasons for quitting their last job. In Belgium, Russia, and Taiwan, they asked about applicants' wage and salary expectations. In Belgium and Russia, they less often asked about applicants' values, opinions, and beliefs. This study suggests that in some countries employment interviews are more than a test of job-related knowledge, skills, and abilities. This report provides a taxonomy that is useful for comparing interview questions in Latin American and other countries as well as directions for future research.